P05.91 Sellar atypical teratoid rhabdoid tumor (ATRT) in an adult: A case report and review of the literature. (19th September 2018) - Barsky, D; Hadelsberg, U; Gonen, L; Margalit, N
Abstract: Background: Atypical teratoid rhabdoid tumor (ATRT) is a rear type of central nervous system (CNS) tumor, which is seen mostly in the pediatric population. However, there are a few dozen of cases reported in adults. This entity was first differentiated from a Wilm's tumor in 1978. Since then much progress has been done in understanding the pathophysiology of this disease, but not has been done in terms of treatment and prognosis, thus ATRT remains a high mortality-disease with grim prognosis and outcome. Material and Methods: a case of 54 year-old female, which presented with symptoms concurrent of a pituitary macroadenoma, which was found out to be a tumor of ATRT characteristics on pathology. Results: the patient underwent surgery, and the tumor was completely removed, in endoscopic transphenoidal approach. Conclusion: ATRT is an uncommon entity, particularly in adults, it is very important to keep it on the differential diagnosis as it has a major influence on disease management, and outcome. Due to ATRT's poor prognosis and its rarity, it is important the patient is treated by a surgeon, oncologist and radiation oncologist as a multimodality treatment increases survival rates.